Methodology of investment attractiveness in the system of the agroindustrial complex - Sambros N.B., Pizengolts V.M., Zharov A.N., Savelyeva I.E., (Opción, 2019)
The article deals with the methodological and methodical aspects of investment attractiveness in the system of an agroindustrial complex in Russia, based on the developed methodological tools. As a result, the level of development of market relations and commercial infrastructure of agribusiness is assessed on the basis of real processes leading to the development of the business climate, as well as the attitude of the authorities to these processes. In conclusion, the final stage of the study of the investment market is the analysis and assessment of the investment attractiveness of agricultural enterprises as potential investment objects.